2008
DOI: 10.1210/en.2008-0016
|View full text |Cite
|
Sign up to set email alerts
|

Central Lipoprivation-Induced Suppression of Luteinizing Hormone Pulses Is Mediated by Paraventricular Catecholaminergic Inputs in Female Rats

Abstract: The present study aims to clarify the role of fatty acids in regulating pulsatile LH secretion in rats. To produce an acute central lipoprivic condition, mercaptoacetate (MA), an inhibitor of fatty acids oxidation, was administered into the fourth cerebroventricle (4V) in ad libitum fed ovariectomized (OVX) rats (0.4, 2, and 10 micromol/rat) with or without an estradiol (E2) implant producing diestrus plasma E2 levels. Pulsatile LH secretion was suppressed by 4V MA administration in a dose-dependent manner in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…57: [379][380][381][382][383][384] 2011) eproductive functions are known to be impaired under malnutrition in both sexes in several mammalian species [1][2][3][4][5]. Fasting, glucoprivation or lipoprivation has been well established to inhibit gonadal functions through suppressing pulsatile luteinizing hormone (LH) secretion in rats [6][7][8][9][10][11][12]. Malnutrition is often accompanied by a high level of circulating ketone bodies, which are by-products of enhanced fatty acid mobilization.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…57: [379][380][381][382][383][384] 2011) eproductive functions are known to be impaired under malnutrition in both sexes in several mammalian species [1][2][3][4][5]. Fasting, glucoprivation or lipoprivation has been well established to inhibit gonadal functions through suppressing pulsatile luteinizing hormone (LH) secretion in rats [6][7][8][9][10][11][12]. Malnutrition is often accompanied by a high level of circulating ketone bodies, which are by-products of enhanced fatty acid mobilization.…”
mentioning
confidence: 99%
“…Numerous studies have indicated that the brain energy sensor resides within the hypothalamus and brainstem [18][19][20][21][22][23]. Previous studies have raised the possibility that brainstem energy sensors sense glucose and fatty acid availability to regulate gonadotropin secretion because administration of 2-deoxyglucose (2DG), a competitive inhibitor of glucose oxidation, or mercaptoacetate (MA), an inhibitor of fatty acid oxidation, into the fourth cerebroventricle (4V) suppresses LH pulses in rats [12,24,25]. Likewise, blockade of hindbrain monocarboxylate transporter 1 (MCT1), a ketone body transporter located in ependymocytes around the 4V, results in normalization of diabetic hyperphagia in rats [26].…”
mentioning
confidence: 99%
See 3 more Smart Citations